Preparation method of easy-graphitizable coating material and application thereof
Patent Information
- Application Number
- CN202510710100.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-05-29
AI Technical Summary
传统包覆沥青在常规热处理温度下(通常低于1200℃)石墨化度较低,影响了锂离子的均匀嵌入/脱出,特别是在高倍率充放电时容易引发局部极化
本发明通过硼掺杂改性显著提升了沥青材料的石墨化性能与电化学特性。硼原子作为电子受体嵌入沥青碳层,催化碳六元环有序排列,使材料在1200℃下即可获得较为有序的炭层结构。同时提升材料导电率,改善锂离子扩散动力学。硼的交联作用还能抑制炭化过程中的结构收缩与微裂纹,使包覆层致密均匀,循环寿命提升。该方法工艺简单,适用于高性能负极包覆材料的低成本制备。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode materials and coated asphalt technology. The invention relates to a method for preparing an easily graphitized coating material and its application. Background Technology
[0002] As the most promising energy storage device today, the performance of lithium-ion batteries directly determines the technological level of key areas such as new energy vehicles, consumer electronics, and energy storage systems. Among the four core components of lithium-ion batteries, the performance of the anode material directly affects the entire battery system. Due to inherent structural imperfections, anode materials often require coating to improve their rate performance and cycle life.
[0003] In the coating process, asphalt coating is applied to the graphite anode material, forming a "protective shield" on the material surface. This not only prevents the co-intercalation and mixing of lithium ions and solvents and inhibits electrolyte decomposition, but also effectively improves the first-charge reversible capacity, cycle stability, and battery rate performance of the anode material. It also helps to shape the anode material, resulting in a larger specific capacity, longer service life, and faster charging speed for the lithium battery.
[0004] Anode material coating technology has been widely used in industry, but existing methods still face technical bottlenecks. Traditional coated bitumen exhibits low graphitization at conventional heat treatment temperatures (typically below 1200℃), affecting the uniform insertion / extraction of lithium ions, especially easily leading to localized polarization during high-rate charge / discharge. The volume shrinkage rate during bitumen carbonization is as high as 60-70%, generating microcracks at the particle interface. These cracks become electrolyte permeation channels, accelerating abnormal SEI film growth. Therefore, it is necessary to develop novel coating materials to simultaneously address the problems of insufficient graphitization and numerous defects caused by low-temperature carbonization. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, this invention provides a method for preparing an easily graphitized coating material and its application. The preparation method provided by this invention significantly improves the graphitization performance of pitch materials through boron doping, enabling the formation of an ordered carbon layer structure at 1200℃, while simultaneously suppressing carbonization shrinkage and microcrack formation, thus improving the density and uniformity of the coating layer. The resulting coating material is suitable for lithium-ion battery anodes, improving the battery's first-charge reversible capacity, cycle stability, and rate performance. This invention features a simple process, low cost, and is suitable for industrial production.
[0006] The above-mentioned objective of this invention is achieved through the following technical solution: A method for preparing an easily graphitized coating material, comprising using one or more of the following as raw materials: petroleum residue oil, ethylene tar, medium-low temperature coal tar, coal tar pitch, petroleum pitch, and soft pitch; adding a blending solvent and a catalyst to obtain a blended raw material; and sequentially performing blending solvent compounding, boron doping, and pressure polymerization, or sequentially performing blending solvent compounding, boron doping, pressure polymerization, oxidative crosslinking, and vacuum distillation / molecular distillation processes to obtain an easily graphitized coating material with a low interlayer spacing (less than 0.348 nm at 1200℃) after carbonization.
[0007] The process of sequentially blending solvents, boron doping, pressure polymerization, oxidative crosslinking, vacuum distillation or molecular distillation yields a graphitizable solid coating material with a low interlayer spacing (less than 0.348 nm at 1200℃) after carbonization.
[0008] The process involves sequentially blending solvents, boron doping, and pressure polymerization to obtain an easily graphitized liquid coating material with a low interlayer spacing (less than 0.348 nm at 1200℃) after carbonization.
[0009] The raw materials account for 50wt% to 100wt% of the blended raw materials, the blending solvent accounts for 0wt% to 50wt% of the blended raw materials, and the catalyst accounts for 0wt% to 1wt% of the blended raw materials.
[0010] The catalyst is a Lewis acid catalyst, preferably any one or more of aluminum chloride, boron trifluoride, trimethylaluminum, and zinc chloride.
[0011] The blend solvent includes one or more of the following: cracked naphthalene fraction or wash oil, and borate ester homologues. The cracked naphthalene fraction accounts for 80 wt% to 99 wt% of the blend solvent, and the borate ester homologues account for 1 wt% to 20 wt% of the blend solvent.
[0012] The borate ester homologues are preferably any one or more of phenylboronic acid, naphthaleneborate, and polyborate.
[0013] The softening point of solid easily graphitized coating materials is 100℃~280℃.
[0014] Furthermore, the blending solvent compounding step specifically includes: adding one or more of the borate ester homologues to the cracked naphthalene fraction or wash oil, stirring at 10-200℃ for 0.5-2 hours to obtain the blended solvent; Furthermore, the boron doping step specifically includes: using one or more of the following as raw materials: petroleum residue oil, ethylene tar, medium-low temperature coal tar, coal tar pitch, petroleum pitch, and soft pitch; adding a blending solvent and a catalyst to obtain a blended raw material; mixing at 50℃~200℃ for 0.5~24h to obtain the doped modified raw material. Furthermore, the pressurized polymerization step specifically includes: placing the doped modified raw material obtained in the boron doping step into a reactor, heating it to 50℃ to 200℃ at a heating rate of 1℃ / min to 10℃ / min, reacting at a constant temperature for 0.5h to 5h, heating it again to 50℃ to 350℃, introducing nitrogen gas to pressurize it to 0.1 to 3.0MPa, and maintaining the polymerization reaction at a constant temperature for 1h to 24h to obtain an easily graphitized liquid coating material; Furthermore, the oxidative crosslinking step specifically includes: subjecting the easily graphitized liquid coating material obtained from the pressure polymerization step to oxidative crosslinking, bubbling air into the liquid coating material at 100℃~380℃, with an air flow rate of 1L / min~300L / min, and an oxidation time of 1h~10h, to obtain oxidized asphalt with a softening point greater than 100℃; Furthermore, the oxidized asphalt obtained after oxidative crosslinking is separated into light fractions by vacuum distillation or molecular distillation, and the heavy aromatic components (polycyclic aromatic hydrocarbon fused ring structure) are enriched to obtain an easily graphitized solid coating material.
[0015] Furthermore, the parameters for vacuum distillation are: vacuum pressure -0.05 to -0.1 MPa, distillation temperature 200℃ to 400℃, stirring speed 0 rpm to 300 rpm, and time 1 h to 10 h.
[0016] Furthermore, the parameters for molecular distillation are: distillation temperature 200℃~330℃, vacuum pressure 10Pa~200Pa, and rotation speed 100rpm~400rpm.
[0017] Furthermore, the stirring speed in the solvent blending and boron doping steps is 0 rpm to 700 rpm.
[0018] The present invention also seeks protection for the application of the easily graphitized liquid coating material or easily graphitized solid coating material prepared by the above preparation method in the preparation of lithium-ion batteries, wherein the easily graphitized solid coating material coats the negative electrode material of the lithium-ion battery.
[0019] The advantages of this invention compared to the prior art are: This invention significantly improves the graphitization performance and electrochemical properties of asphalt materials through boron doping modification. Boron atoms act as electron acceptors, embedding into the carbon layer of the asphalt and catalyzing the orderly arrangement of the six-membered carbon rings, enabling the material to achieve a relatively ordered carbon layer structure at 1200℃. Simultaneously, it enhances the material's conductivity and improves lithium-ion diffusion kinetics. The cross-linking effect of boron also suppresses structural shrinkage and microcracks during carbonization, resulting in a dense and uniform coating layer and improved cycle life. This method is simple and suitable for the low-cost preparation of high-performance anode coating materials.
[0020] This invention significantly optimizes the doping effect through the synergistic effect of borate ester homologues with asphalt ester solvents such as cracked naphthalene fraction and wash oil. Cracked naphthalene fraction, as an excellent solvent, can fully dissolve asphalt raw materials, while its rich aromatic structure provides a uniform dispersion medium for borate esters, ensuring uniform boron doping in asphalt molecules. During blending, borate esters undergo transesterification with the active sites of asphalt, forming stable BOC bonds, which not only improves the boron doping efficiency but also enhances the cross-linking network of asphalt molecules. This process achieves boron dispersion under mild conditions, avoiding component segregation caused by high-temperature treatment and providing a uniform precursor structure for subsequent carbonization.
[0021] The catalyst used in this invention is a Lewis acid catalyst, which can activate boron atoms in borate esters, making them more likely to react with aromatic rings or aliphatic side chains in asphalt. Boron atoms can be effectively embedded in the carbon skeleton of asphalt, significantly improving material properties.
[0022] This invention allows for the flexible preparation of liquid or solid coating materials using the same process. Liquid materials are suitable for impregnation or spraying processes, achieving uniform coating of complex morphologies; solid materials are easily pulverized and then coated in a solid phase, meeting the needs of different application scenarios. Both forms retain their easy graphitization properties, significantly reducing production costs and improving process adaptability. Detailed Implementation
[0023] The present invention is further illustrated below by way of embodiments, but these embodiments are not intended to limit the invention to their scope. Any simple modifications, equivalent changes, or alterations made by those skilled in the art based on the embodiments of the present invention without inventive effort are still within the scope of protection of the present invention.
[0024] A method for preparing an easily graphitized coating material, comprising the following steps: using one or more of petroleum residue oil, ethylene tar, medium-low temperature coal tar, and coal tar pitch as raw materials, adding a blending solvent and a catalyst, and sequentially performing blending solvent compounding, boron doping, pressure polymerization, oxidative crosslinking, and vacuum distillation or molecular distillation processes to obtain an easily graphitized coating material with a low interlayer spacing (less than 0.348 nm at 1200℃) after carbonization; 1) Blending solvent formulation Add one or more of the borate ester homologues to the cracked naphthalene fraction or wash oil, place it in a reaction vessel and stir at 10-200℃ for 0.5-2h to obtain a blended solvent; 2) Boron doping A doped and modified raw material is prepared by using one or more of the following as raw materials: petroleum residue, ethylene tar, petroleum pitch, medium-low temperature coal tar, coal pitch, and soft pitch, adding a blending solvent and a catalyst, mixing at a temperature of 50℃ to 200℃, and for a mixing time of 0.5 to 24 hours. 3) Pressure polymerization The doped and modified raw material is placed in a reactor and heated to 50℃~200℃ at a heating rate of 1℃ / min~10℃ / min. The temperature is kept constant for 0.5h~5h. The temperature is then raised again to 50℃~350℃, and nitrogen gas is introduced to pressurize to 0.1~3.0MPa. The polymerization reaction is kept constant for 1h~24h to obtain an easily graphitized liquid coating material. 4) Oxidative crosslinking The easily graphitized liquid coating material is further subjected to oxidative crosslinking at a temperature of 100℃~380℃, with air being blown in at a flow rate of 1L / min~300L / min and an oxidation time of 1h~10h, to obtain oxidized asphalt with a softening point greater than 100℃. 5) Further processing (reduced pressure distillation or molecular distillation) The oxidized asphalt was separated into light and heavy components by vacuum distillation or molecular distillation. The parameters used for vacuum distillation are as follows: Pressure reduction: -0.05~-0.1Mpa; Distillation temperature: 200℃~400℃; Stirring speed: 0 rpm to 300 rpm; Time: 1 hour to 10 hours; Molecular distillation, performed under rotational conditions, yields oxidized bitumen. The parameters used are as follows: Distillation temperature: 200℃~330℃; Vacuum pressure: 10Pa~200Pa; Speed: 100rpm~400rpm; Easily graphitizable coating materials are prepared by vacuum distillation or molecular distillation.
[0025] The cracked naphthalene fraction accounts for 80 wt% to 99 wt% of the blend solvent, and the borate ester homologue accounts for 1 wt% to 20 wt% of the blend raw materials.
[0026] In the doping modification step, the raw materials petroleum residue, ethylene tar, petroleum pitch, medium-low temperature coal tar, coal pitch, and soft pitch account for 50wt% to 100wt% of the blended raw materials, the blending solvent accounts for 0wt% to 50wt% of the blended raw materials, and the catalyst accounts for 0wt% to 1wt% of the blended raw materials.
[0027] The catalyst is a Lewis acid catalyst, preferably any one of zinc chloride, aluminum chloride, boron trifluoride, and trimethylaluminum.
[0028] The stirring speed in the solvent blending and boron doping steps is 0 rpm to 700 rpm.
[0029] The softening point of the easily graphitized coating material obtained by vacuum distillation or molecular distillation is 100℃~280℃. Example
[0030] Arylboronic acid ester was added to the cracked naphthalene fraction, with a mass percentage of 90 wt% to 10 wt% arylboronic acid ester. The mixture was placed in a reactor and stirred at 120°C for 2 hours to ensure thorough mixing of the two raw materials and obtain a blended solvent. 70 wt% ethylene tar and 30 wt% blended solvent were mixed evenly and placed in a reactor. The mixture was stirred at 150°C for 1 hour to ensure thorough mixing of the ethylene tar and blended solvent, thus obtaining a doped and modified raw material. The doped and modified raw material was placed in a reactor and heated to 200°C at a rate of 5°C / min, held at that temperature for 1 hour, then heated again to 330°C and pressurized to 0.5 MPa with nitrogen gas. The polymerization reaction was held at that temperature for 4 hours to obtain an easily graphitized liquid coating material. The easily graphitized liquid coating material was subjected to oxidative crosslinking at 330°C for 3 hours to obtain oxidized asphalt. Oxidized asphalt was added to a short-path molecular still, the temperature was set at 280℃, the vacuum pressure of the short-path molecular still was controlled at 100Pa, the rotation speed was 200rpm, and the distillation time was 3h to obtain an easily graphitizable coated asphalt material. Performance indicators are shown in Table 1, and performance indicators after carbonization at 1200℃ are shown in Table 2. This easily graphitizable coated asphalt material was then solid-phase coated with a negative electrode material, carbonized, and assembled into a coin cell lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3. Example
[0031] Arylboronic acid ester was added to the cracked naphthalene fraction, with a mass percentage of 90 wt% to 10 wt% arylboronic acid ester. The mixture was placed in a reactor and stirred at 120°C for 2 hours to ensure thorough mixing of the two raw materials and obtain a blended solvent. 70 wt% ethylene tar and 30 wt% blended solvent were mixed evenly and placed in a reactor. The mixture was stirred at 150°C for 1 hour to ensure thorough mixing of the ethylene tar and blended solvent, thus obtaining a doped modified raw material. The doped modified raw material was placed in a reactor and heated to 200°C at a rate of 5°C / min. The temperature was maintained for 1 hour, then raised again to 330°C, pressurized to 0.5 MPa with nitrogen, and the polymerization reaction was maintained at this temperature for 4 hours to obtain an easily graphitized liquid-coated material. The performance indicators are shown in Table 1, and the performance indicators after carbonization at 1200℃ are shown in Table 2. The easily graphitized asphalt material and the negative electrode material were liquid-phase coated and carbonized, and then assembled into a button lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3. Example
[0032] Polyboronic acid ester was added to the cracked naphthalene fraction, with a mass percentage of 95 wt% to 5 wt% polyboronic acid ester. The mixture was placed in a reactor and stirred at 150°C for 2 hours to ensure thorough mixing of the two raw materials and obtain a blended solvent. Ethylene tar (70 wt% of the blended raw materials) and the blended solvent (30 wt% of the blended raw materials) were mixed evenly and placed in a reactor. The mixture was stirred at 150°C for 1 hour to ensure thorough mixing of the ethylene tar and the blended solvent, thus obtaining a doped and modified raw material. The doped and modified raw material was placed in a reactor and heated to 200°C at a rate of 5°C / min. The temperature was maintained for 1 hour, then raised to 350°C and pressurized to 0.6 MPa with nitrogen gas. The polymerization reaction was maintained at this temperature for 2 hours to obtain an easily graphitized liquid coating material. The easily graphitized liquid coating material was subjected to oxidative crosslinking at 330°C for 3 hours to obtain oxidized asphalt. Oxidized asphalt was added to a short-path molecular still, the temperature was set at 300℃, the vacuum pressure of the short-path molecular still was controlled at 100Pa, the rotation speed was 200rpm, and the distillation time was 3h to obtain an easily graphitizable coated asphalt material. Performance indicators are shown in Table 1, and performance indicators after carbonization at 1200℃ are shown in Table 2. This easily graphitizable coated asphalt material was then solid-phase coated with a negative electrode material, carbonized, and assembled into a coin cell lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3. Example
[0033] Arylboronic acid ester was added to the cracked naphthalene fraction, with a mass percentage of 85 wt% to 15 wt% arylboronic acid ester. The mixture was placed in a reactor and stirred at 120°C for 2 hours to ensure thorough mixing of the two raw materials and obtain a blended solvent. 70 wt% ethylene tar, 29 wt% blended solvent, and 1 wt% zinc chloride were mixed evenly and placed in a reactor. The mixture was stirred at 100°C for 1 hour to ensure thorough mixing of the ethylene tar and blended solvent, thus obtaining a doped modified raw material. The doped modified raw material was placed in a reactor and heated to 200°C at a rate of 5°C / min, held at that temperature for 1 hour, then heated again to 330°C and pressurized to 0.5 MPa with nitrogen gas. The polymerization reaction was held at that temperature for 4 hours to obtain an easily graphitized liquid coating material. The easily graphitized liquid coating material was subjected to oxidative crosslinking at 300°C for 3 hours to obtain oxidized asphalt. Oxidized asphalt was added to a short-path molecular still, the temperature was set at 300℃, the vacuum pressure of the short-path molecular still was controlled at 100Pa, the rotation speed was 200rpm, and the distillation time was 3h to obtain an easily graphitizable coated asphalt material. Performance indicators are shown in Table 1, and performance indicators after carbonization at 1200℃ are shown in Table 2. This easily graphitizable coated asphalt material was then solid-phase coated with a negative electrode material, carbonized, and assembled into a coin cell lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3.
[0034] Comparative Example 1 Ethylene tar was placed in a reactor and heated to 350℃ at a heating rate of 5℃ / min for polymerization. After holding at this temperature for 4 hours, the mixture was added to a short-path molecular distillation apparatus. The temperature was set at 250℃, the vacuum pressure of the short-path molecular distillation apparatus was controlled at 100 Pa, the rotation speed at 200 rpm, and the distillation time was 1 hour to obtain an easily graphitized low-softening-point coated pitch material. Performance indicators are shown in Table 1, and performance indicators after carbonization at 1200℃ are shown in Table 2. This easily graphitized coated pitch material was then solid-phase coated with a negative electrode material, carbonized, and assembled into a coin-type lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3.
[0035] Comparative Example 2 Ethylene tar was placed in a reactor and heated to 380℃ at a heating rate of 5℃ / min for polymerization. After holding at this temperature for 2 hours, the mixture was added to a short-path molecular distillation apparatus. The temperature was set at 280℃, the vacuum pressure of the short-path molecular distillation apparatus was controlled at 100 Pa, the rotation speed was 200 rpm, and the distillation time was 3 hours to obtain an easily graphitized low-softening-point coated pitch material. Performance indicators are shown in Table 1, and performance indicators after carbonization at 1200℃ are shown in Table 2. This easily graphitized coated pitch material was then solid-phase coated with a negative electrode material, carbonized, and assembled into a coin-type lithium-ion battery for electrochemical testing. The battery test results are shown in Table 3.
[0036] Table 1 Performance Indicators of Examples Example 1 226.7 0.07 69.6 Example 2 none 0.03 10.2 Example 3 276.3 0.11 74.3 Example 4 280.8 0.86 76.1 Comparative Example 1 151.7 0.02 61.2 Comparative Example 2 247.1 0.01 73.6 Table 2 Performance indicators after carbonization at 1200℃ Example 1 3.4721 0.89 Example 2 3.4791 0.89 Example 3 3.4582 0.87 Example 4 3.4371 0.85 Comparative Example 1 3.5011 0.90 Comparative Example 2 3.4928 0.90 Table 3 Battery Test Results negative electrode material standard 12.1 3.88 354.1 92.6 Example 1 14.6 2.17 353.7 94.7 Example 2 13.8 2.03 355.2 95.5 Example 3 14.1 2.26 352.9 94.1 Example 4 15.1 3.11 356.2 95.9 Comparative Example 1 14.7 2.62 353.2 94.1 Comparative Example 2 14.1 2.41 355.0 94.8 As shown in Table 2, the interlayer spacing (d002) of Examples 1-4 after carbonization at 1200℃ is lower than that of Comparative Examples 1 and 2, especially the interlayer spacing of Example 4, which is only 3.4371 Å, far superior to the 3.5011 Å and 3.4928 Å of the Comparative Examples. This indicates that boron doping effectively promotes the ordered arrangement of the six-membered carbon rings, forming a more dense graphitized structure. Furthermore, Example I... D / I G The ratios were generally lower than those of the control group, further demonstrating the increased degree of graphitization.
[0037] Regarding electrochemical performance, as shown in Table 3, the coated anode materials in Examples 1-4 all outperformed the uncoated anode material standard in terms of initial coulombic efficiency, with Example 4 reaching 95.9%, significantly higher than the comparative example's 92.6%. Simultaneously, the reversible specific capacity of the examples was comparable to or even slightly improved compared to the standard, indicating that the coated material of the present invention improves battery performance without sacrificing capacity. In contrast, while the comparative examples also exhibited certain performance characteristics, they were inferior to the examples of the present invention in terms of graphitization degree and electrochemical performance.
[0038] The embodiments described above are merely preferred embodiments of the present invention, and not all feasible embodiments of the present invention. Any obvious modifications made by those skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing an easily graphitized coating material, characterized in that, The method uses one or more of the following as raw materials: petroleum residue, ethylene tar, medium-low temperature coal tar, coal tar pitch, petroleum pitch, and soft pitch. A blending solvent and a catalyst are added to obtain a blended raw material. This material is then subjected to a blending solvent compounding process, boron doping, and pressure polymerization, or a blending solvent compounding process, boron doping, pressure polymerization, oxidative crosslinking, and vacuum distillation / molecular distillation process, to obtain a carbonized, easily graphitized coating material with a low interlayer spacing. The low interlayer spacing is less than 0.348 nm at 1200℃. The catalyst is a Lewis acid catalyst; the blending solvent includes cracked naphthalene fractions or wash oil, and borate ester homologues.
2. The method for preparing an easily graphitized coating material as described in claim 1, characterized in that, The raw materials account for 50wt%-100wt% of the blended raw materials, the blending solvent accounts for 29wt%-50wt% of the blended raw materials, and the catalyst accounts for 0wt%-1wt% of the blended raw materials.
3. The method for preparing an easily graphitized coating material as described in claim 1, characterized in that, The specific steps of the blending solvent preparation include: adding one or more of the borate ester homologues to the cracked naphthalene fraction or wash oil, stirring at 10-200℃ for 0.5-2h to obtain the blending solvent; The boron doping step specifically includes: using one or more of the following as raw materials: petroleum residue oil, ethylene tar, medium-low temperature coal tar, coal tar pitch, petroleum pitch, and soft pitch; adding a blending solvent and a catalyst to obtain a blended raw material; mixing at 50℃-200℃ for 0.5-24h to obtain the doped modified raw material. The pressurized polymerization step specifically includes: placing the doped modified raw material obtained in the boron doping step into a reactor, heating it to 50℃-200℃ at a heating rate of 1℃ / min-10℃ / min, reacting at a constant temperature for 0.5h-5h, heating it again to 50℃-350℃, introducing nitrogen gas to pressurize it to 0.1-3.0MPa, and maintaining the polymerization reaction at a constant temperature for 1h-24h to obtain an easily graphitized liquid coating material; The oxidative crosslinking step specifically includes: oxidatively crosslinking the easily graphitized liquid coating material obtained from the pressure polymerization step, bubbling air into the liquid coating material at 100℃-380℃ with an air flow rate of 1L / min-300L / min, and an oxidation time of 1h-10h to obtain oxidized asphalt with a softening point greater than 100℃.
4. The method for preparing an easily graphitized coating material as described in claim 3, characterized in that, The oxidized asphalt obtained after oxidative crosslinking is separated into light fractions by vacuum distillation or molecular distillation, and the heavy aromatic components are enriched to obtain an easily graphitized solid coating material.
5. The method for preparing an easily graphitized coating material as described in claim 1, characterized in that, The parameters for vacuum distillation are: vacuum pressure -0.05 to 0.1 MPa, distillation temperature 200℃ to 400℃, stirring speed 0 rpm to 300 rpm, and time 1 h to 10 h.
6. The method for preparing an easily graphitized coating material as described in claim 1, characterized in that, The parameters for molecular distillation are: distillation temperature 200℃-330℃, vacuum pressure 10Pa-200Pa, and rotation speed 100rpm-400rpm.
7. The method for preparing an easily graphitized coating material as described in claim 1, characterized in that, The cracked naphthalene fraction accounts for 80wt%-99wt% of the blend solvent, and the borate ester homologues account for 1wt%-20wt% of the blend solvent.
8. The application of the easily graphitized coating material prepared by the method for preparing an easily graphitized coating material according to any one of claims 1-7 in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
A boron doping modified soft carbon coating negative electrode material with high stability under high and low temperature environment and a preparation method thereof
CN109167025A
Coating agent, coated modified graphite negative electrode material, preparation method and application of coated modified graphite negative electrode material, and lithium ion battery
CN112768691A